Pengaruh Gross Profit Margin dan Net Profit Margin Terhadap Pertumbuhan Laba PT Mustika Ratu Tbk - Muhammad Saiful Islam; Nurhayati Nurhayati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine and analize the effect of Gross Profit Margin (GPM) and Net Profit Margin (NPM) on profit growth. This type of research is associative. The population used in this study is PT. Mustika Ratu, Tbk for 24 years, from 1994 - 2018. The sampling technique used was purposive sampling with a sample of 8 years. Data collection techniques used in this study are literature and documentation studies, data analysis techniques used are multiple linear regression, multiple linear correlation, determination test and partial t test and f test. The results of this study indicate that GPM and NPM partially do not affect earnings growth, and simultaneously GPM and NPM do not affect earnings growth